The Relationship Between Sleep Quality and Overweight in Physiotherapy Students of Faculty of Medicine, Udayana University - Dwitia Putri, Thania; Ni Wayan Tianing; Putu Ayu Sita Saraswati; M. Widnyana (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: In students who experience a decrease in sleep quality due to dense academic and non-academic lecture activities. Students who experience a decrease in poor sleep quality have unhealthy body conditions such as insomnia and other sleep disorders such as overweight body mass index. Objective: The purpose of this study was to determine the relationship between sleep quality and overweight physiotherapy students at the Faculty of Medicine, Udayana University. Method: In students who experience a decrease in sleep quality due to dense academic and non-academic lecture activities. Students who experience a decrease in poor sleep quality have unhealthy body conditions such as insomnia and other sleep disorders such as overweight body mass index. The purpose of this study was to determine the relationship between sleep quality and overweight of physiotherapy students at the Faculty of Medicine, Udayana University. Results: The results of the study of sleep quality with overweight obtained a sample of research with poor sleep quality, namely 41 people (58.6%) and good sleep quality as many as 29 people (41.4%) for body mass index that was not overweight as many as 27 people (38.6%) and overweight as many as 43 people (61.4%). Through a chi square test to test the hypothesis of the researcher. The result obtained is the value of p = 0.000 so that p < 0.05. It can be concluded that there is a significant relationship between sleep quality and overweight of Physiotherapy students of the Faculty of Medicine, Udayana University. Conclusion: There is a relationship between sleep quality and overweight in physiotherapy students at the Faculty of Medicine, Udayana University.